Allopolyploidy in the Wintergreen Group of tribe Gaultherieae (Ericaceae) inferred from low‐copy nuclear genes. (25th June 2019) - Lu, Lu; Fritsch, Peter W.; Bush, Catherine M.; Wang, Hong; Kron, Kathleen A.; Li, De‐Zhu
Abstract : DNA sequence data from the low‐copy nuclear genes waxy (GBSSI) and leafy were compared with plastid and ITS sequence data from prior studies to reconstruct phylogenetic relationships in the Wintergreen Group of tribe Gaultherieae (Ericaceae). We conducted phylogenetic analysis with 102 species that includes representatives of all 15 major clades previously identified within the Wintergreen Group and that together span its circum‐Pacific distribution. Results yielded two distinct homeologous copies of waxy for two of the clades, each in widely separated parts of the tree. It also yielded two copies of leafy for one of the clades; only one copy of leafy was found for the other clade, but it was placed in the same major clade as its waxy counterpart and well away from its placement in a prior plastid analysis. A combined four‐locus ( waxy, leafy, ITS and plastid data) phylogenetic analysis of all available relevant data placed the copies of each of the clades in two distinct positions in the phylogeny with strong overall statistical support. In combination with evidence from morphology, reproductive biology and cytology, the results suggest that these clades arose through allopolyploid hybridization between lineages deep in the phylogeny but relatively close geographically. This finding confirms previous assumptions that hybridization has played an important role in the evolution of the Gaultherieae.